Transitional justice and the public sphere: engagement, legitimacy and contestation - Brants, Chrisje; Karstedt, Susanne (Oñati international series in law and society, 2017)
This book looks at the question of transparency within the framework of transitional justice. The collection analyses the issue from socio-legal, cultural studies and practitioner perspectives. Taking a three-part approach, it firstly discusses basic principles guiding justice globally before exploring courts and how they make justice visible. Finally, the collection reviews the interface between law, transitional justice institutions and the public sphere